Round-Robin Tournaments in the Lab: Lottery Contests vs. All-Pay Auctions - Arne Lauber; Christoph March; Marco Sahm (CESifo GmbH, 2025)
We conduct a laboratory experiment to compare the fairness and intensity of round-robin tournaments with three symmetric players, a single prize, and two alternative match formats. Matches are either organized as lottery contests or all-pay auctions. Whereas we confirm the theoretical prediction that tournaments are less fair if matches are organized as all-pay auctions, we reject the predicted difference in tournament intensity. Moreover, the reason for the reduced fairness of tournaments based on all-pay auctions is also at odds with theory. In the lab, such tournaments heavily disfavor (in payoff-terms) the player acting in the final two matches. The reason is the substantially weaker than predicted discouragement of this player when competing first against the loser of the first match. Subjects try to exploit a perceived negative psychological momentum in such situations but only manage to end up in a dissipation trap: an effort-intense, final-like last match which significantly reduces their payoffs.
Keywords: C72; C91; D72; Z20; 330; sequential round-robin tournaments; lottery contest; all-pay auction; laboratory experiment; discouragement effect; dissipation trap